Clinical profile, dietary zinc content, and lifestyle habits of adult male and female hbss and hbsc patients - Alaka, Anuoluwapo Abisola; Alaka, Olubunmi Olayemi; Iyanda, Ayobola Abolape (Bangladesh Journal of Medical Science, 2024)
Objective: Males and females have been reported to show significant variation with respect to clinical profile of sickle cell disease (SCD) (e.g. cardiovascular, musculoskeletal and chronic end-organ complications). Clinical features of SCD are also influenced by lifestyle and dietary habits. Thus, the study was conducted to examine whether the distributions of other manifestations (e.g. priapism, pain frequency, leg ulcers rates) and habits (lifestyle, dietary) of SCD patients in Osun state, Nigeria are influenced by gender or genotype. Material and methods: Questionnaires were administered to obtain information on age, gender, concoction/herbal preparations, and fruit/vegetable consumption, as well as zinc contents of 24-hour meal recall, physical exercise, lifestyle parameters and clinical profile of SCD. Descriptive (relative frequency) and inferential (Chi-square (χ2) test of independence) statistics were employed. Statistical significant was set at p<0.05. Results and discussion: HbSS rather than HbSC showed higher distributions of pain frequency and more frequent hospitalization rates at p= .001 and p=.001 respectively. There was no significant relationship between hemoglobin genotype and the following variables: leg ulcers, priapism, fruit intake, herb/concoction consumption, 24-hour dietary zinc content. Moreover, all the variables were not influenced by gender not only among HbSS but also HbSC patients. Conclusion: There are indications from data obtained that clinical profile of SCD such as priapism, leg ulcers, high hospitalization rates and pain episodes are present among HbSS and HbSC SCD patients in Osun state Nigeria. Although only pain episodes and hospitalization rates were significantly higher among HbSS than HbSC, for either variable though there was no gender bias in its distribution. Similarly the distributions of other variables (such as exercise, dietary, etc) for each of SCD (HbSS, HbSC) categories were not influenced by gender. Bangladesh Journal of Medical Science Vol. 23 No. 01 January’24 Page : 74-82